Clinical and radiographic evaluation of Ponseti method for neonate congenital clubfoot - Jiang, Hai; Li, Tao (Frontiers in Pediatrics, 2025)
ObjectiveThe objective of this study was to evaluate the clinical and radiographic outcomes of children with congenital clubfoot following treatment with the Ponseti method.MethodsWe conducted a retrospective analysis of radiographic data from 20 children (12 males and 8 females) aged between 2 years 6 months and 7 years who underwent Ponseti method treatment for congenital clubfoot. The beginning treatment age was below 4 weeks after birth. The study included bilateral ten cases and unilateral ten cases. There were 20 cases which age matched normal feet in control group. The Pirani scoring system was used to assess the severity of the clubfeet. The average Pirani score was 5.5 (4.5–6). Radiographic measurements were taken from post-treatment images and compared to normative values. Talar length, talar height, calcaneus inclination angle, Meary's angle, and talocalcaneal angle were measured. Paired t-tests and effect size (r) were used to evaluate the effectiveness of the treatment.ResultsAll the patients were followed up at average 44 months (30–84 months). Functional, plantigrade feet with adequate mobility were achieved in all patients. The average Pirani score was 0.075 (0–0.5) at the end of the follow- up. Bilateral clubfoot exhibited significantly shorter talar length, lower talar height, smaller talocalcaneal angles, smaller calcaneus inclination angles and smaller Meary's angles compared to normal feet. Unilateral clubfeet exhibited a significantly greater talar height and a slightly higher calcaneus inclination angles compared to bilateral clubfeet. There were no significant differences observed in talar length, talocalcaneal angle, or Meary's angle between bilateral and unilateral clubfoot groups.ConclusionsThe Ponseti method has been proven to be highly effective in achieving functional correction in children with congenital clubfoot. However, radiographic images in this study revealed differences in tarsal bone morphology. Therefore, further long-term studies are necessary to evaluate the durability of these corrections and their impact on functional mobility in adulthood. The future study should also aim to clarify the causes of observed morphological alterations.